Utility of Leflunomide in the Treatment of Drug Resistant Cytomegalovirus Retinitis. (2nd January 2017) - Rifkin, Lana M.; Minkus, Caroline L.; Pursell, Kenneth; Jumroendararasame, Chaisiri; Goldstein, Debra A.
ABSTRACT: Purpose : To describe leflunomide use in the treatment of drug resistant cytomegalovirus retinitis. Leflunomide has been shown to be effective in the treatment of systemic CMV viremia. Methods : Retrospective chart review of patients with CMV retinitis treated with leflunomide. Results : Two HIV-negative organ transplant recipients with UL 97 mutation resistant-genotype CMV were identified. Patient 1 developed CMV viremia post-kidney transplant and subsequently bilateral CMV retinitis. Retinitis progressed, despite intravitreal injection of ganciclovir and foscarnet, and IV foscarnet and oral valganciclovir. Retinitis control was achieved with the addition of oral leflunomide. Disease remained inactive for 22 months. Patient 2 developed CMV retinitis after lung transplant. Disease progressed despite intravitreal foscarnet injections and oral valganciclovir. Control of retinitis was achieved with addition of oral leflunomide, allowing cessation of intravitreal therapy. Disease remained inactive until his death. Conclusions : Leflunomide may be considered as a treatment option for resistant CMV retinitis.